The role of school leadership in promoting ethical behaviour in two schools in Ekurhuleni North District - Chanyandura, Joyce (My University, 2020)
This research on ethical leadership was carried out at two church schools that are located in the Ekurhuleni North District in Gauteng. The study was a multiple case in two different settings and it adopted the qualitative approach underpinned by the interpretive paradigm. The study was underpinned by Shapiro and Stefkovich`s (2016) Multiple Ethical Paradigm comprising the four dimensions which are: the ethic of justice, ethic of critique, ethic of care and ethic of the profession. The core objective of my study was to explore the key role of school leadership in the promotion of ethical behaviour in the researched schools. To obtain rich informants, I utilised the purposive and convenience sampling methods. For data generation, I employed three different data generation methods, which are semi-structured interviews, questionnaires, and documents reviews. During data analysis, I generated themes and sub-themes from the findings, which further informed my conclusions and furthermore my recommendations. Findings from my study suggest that both the school leaders and the educators had fair understanding of ethical leadership, which they associated with acting with fairness, respect, treating individuals as unique beings and school leaders acting as role models. Nevertheless, the school leaders cited some challenges in the implementation of ethical behaviour, such as inter alia, some educators who do not comply with the school rules and code of conduct, and collective negativism from teachers. The majority of staff members seemed unhappy about unfair treatment, favouritism, inconsistency and their principals not being role models to them. Several recommendations have been made which include, school codes of ethics and the policies be explicitly stated in black and white, and vividly explained to all stakeholders, ethics consent forms to be used during recruitment and appointment processes; suggestion boxes to be installed in the school to curb collective negativity. Further recommendation was made to bring back the general Christian principles into our SA schools` system.
A research report submitted in fulfilment of the academic requirements for the degree of Master of Education to the School of Education in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020